Morbidity and mortality weekly report, Vol. 28, no. 1, January 12, 1979 - Center for Disease Control
Current trends: Highlights of the Surgeon General's report on smoking and health -- Epidemiologic notes and reports: Trichinosis associted with bear meat - Alaska, California. Table 1. Mortality ratio of current cigarette-only smokings, by cause of death, in 8 prospective epidemiologic studies -- Table 2. Estimates of the percentage of current, regular cigarette smokers, adults, United States, 1964-1978. Table I. Cases of specified notifiable diseases: United States -- Table II. Notifiable diseases of low frequency, United States -- Table III. Cases of specified notifiable diseases, United States, weeks ending January 6, 1979, and January 7, 1978 (1st week) -- Table IV. Deaths in 121 U.S. cities, week ending January 6, 1979 (1st week).